The Paradigm of Cosmovision – Based Conservation - Agung, Anak Agung Gde; Suprina, Rina; Pusparini, Marissa (Institut Pariwisata Trisakti, 2019)
The purpose of this article is to try to explain the benefits that can be obtained by learning the traditional knowledge of indigenous people around the world to overcome current perceptions and practices about the environment that has experienced serious degradation. Traditional Ecological Knowledge offers the appropriate tools to learn more the insights of “Sacred Balance”. The research method used in this article was an in-depth analysis of the literature written by experts in the fields of biodiversity, culture, anthropology and ethnography. Synthesis has been taken from the review of this literature as described in this article with various modifications from field verification. This verification has been carried out in Bali through panel discussions with the heads and members of the banjar (village association) in Gianyar, Jatiluwih, Kerobokan and Ubud. The panel's focus was on the concept and practice of